Subcutaneous panniculitis-like lymphoma in a 3-year-old child - Sudharani Chintagunta; Geetakiran Arakkal; Shahana Mohammed; Premajyothi Gopidi (Wolters Kluwer Medknow Publications, 2017)
Panniculitis-like T-cell lymphoma is a rare cytotoxic T-cell lymphoma of the skin involving the subcutaneous tissue. We report panniculitis like lymphoma occurring in a 3 year old female child.She presented with multiple erythematous tender nodules and plaques on face,right thigh and genital region associated with systemic symptoms.The histopathology revealed lobular panniculitis composed of atypical lymphocytes . Immunophenotypic studies showed that the atypical lymphocytes are positive for CD3&CD8 and negative for CD20. The child improved with systemic antibiotics and supportive therapy. Now child is on regular follow up for the past four months without any new lesions.